Pengembangan Profesi Berkelanjutan Guru SMA Negeri Kota Kendari - Rahmawati Rahmawati; Nurzaima Nurzaima; Nasir Nasir (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2019)
Technological developments convey a change to all lines of people; human behavior, ways of life, transportation, habits to the way of learning is also influenced by these developments. In previous phases, education was a one-way process, where the teacher became the only source of information or knowledge for students. More than that, students first know information that occurs in other hemispheres compared to the teacher. This can happen if the teachers are unable to adapt to technological developments. The concept of sustainable professional development is a system that will create a new culture so that teachers can be aware of the changes that occur. This research explores the implementation of sustainable professional development in high schools throughout Kendari City. To obtain the data in question, the researcher used the snowball approach through interviewing, observation, and analysis data. Furthermore, the collected data is analyzed using an interactive model which includes: data reduction, data presentation, and drawing conclusions and verification. The results of this study are: 1) the teachers have an awareness to adapt to the situation, especially knowing and applying up-to-date teaching methods, of course through the development of continuous professionalism; 2) In order to achieve the quality of education, it must be supported by the development of teacher competencies such as PKB, because it will improve teacher competencies to achieve the competency standards set out in applicable laws and regulations, update teacher competencies to meet teacher needs in the development of science, technology and art to facilitate the learning process of students, increase the commitment of teachers in carrying out their main tasks and functions as professionals, foster a sense of love and pride as persons with teacher professions, enhance the image, dignity and dignity of the teaching profession in the community.